"Unraveling the mysteries of the oblique retinacular ligament: A review of its anatomy and biomechanical characteristics" - Mattia Bulli; Paolo Boccolari; Danilo Donati; Roberto Tedeschi (Elsevier, 2024)
Introduction: The oblique retinacular ligament (ORL) has fascinated researchers since its first detailed description by Landsmeer in 1949. Integral to the sophisticated mechanics of finger movements, its anatomical presence and function have sparked extensive debate. Despite initial doubts about its existence, it is now recognized as a crucial structure within the hand's biomechanical system. Materials and methods: A review was conducted to collate primary studies on the ORL, focusing on cadaveric anatomy and biomechanical analyses. Modern dissection techniques and equipment have facilitated the identification of the ORL in virtually all examined samples, moving past earlier challenges of isolating such minute structures. Results: Research elucidates the ORL's dynamic role in coordinating movements between the proximal and distal interphalangeal joints, contradicting earlier theories that deemed it a mere static stabilizer. Recent findings, especially those by Balakrishnan et al., highlight a complex cross structure that allows the ORL to maintain its functional relevance across various joint positions. This challenges previous notions and underscores its significance in finger extension mechanisms. Conclusion: The journey to understand the ORL underscores its pivotal role in hand biomechanics, transforming from a structure of ambiguous existence to a key element in finger movement coordination. This shift in understanding opens new possibilities for therapeutic approaches to hand deformities, emphasizing the ORL's critical function in both anatomical and clinical contexts. As research progresses, it continues to reveal the ORL's complex contributions to hand dynamics, offering insights that promise to enhance outcomes in hand surgery and rehabilitation.